Treatment outcomes of alcohol use disorder by traditional medicine practitioners using plant derivatives in southwestern Uganda: findings from in-depth interviews - Maling, Samuel; Kabakyenga, Jerome; Muchunguzi, Charles; Olet, Eunice Apio; Alele, Paul Erasmus (Frontiers in Psychiatry, 2023)
Background: Globally, 5.1% of the global burden of disease and injury is attributable to alcohol in addition to its significant negative socio-economic impact. Uganda is ranked among the highest alcohol consuming countries in Africa with a reported alcohol per capita consumption of 9.5 liters, much higher than the 6.3 for the African region. Additionally, almost 10% of Ugandans aged 18 and older have an alcohol use disorder. African traditional medicine plays an important role towards universal health coverage in sub-Saharan Africa especially in rural areas. Anecdotal evidence shows that herbal medicines are used by Traditional Medicine Practitioners (TMPs) to treat alcohol drinking problems in Uganda. Data on the outcomes of alcohol treatment by TMPs is scarce. We aimed at documenting the treatment outcomes and secondary benefits of people treated by TMPs using plant derivatives in southwestern Uganda.Methods: This was a cross-sectional semi-structured qualitative study that investigated alcohol drinking history and treatment outcomes of adults living in Bushenyi district, southwestern Uganda. We used a semi-structured questionnaire to conduct face-to-face in-depths interviews with individuals who had been treated for alcohol drinking problems by TMPs using plant derivatives. Three trained research assistants collected the data using audio recordings backed by field notes. The audio recordings were transcribed verbatim and two independent researchers coded the transcripts guided by a priori themes developed by the research team.We conducted 44 in-depths interviews, majority of the participants (70.5%, 31/44) were male with a mean age of 47 years. Most participants (86.2%, 38/44) consumed spirits in addition to other types of alcohol and the mean duration of alcohol drinking before seeking treatment was 14 years. Most participants (93.3%, 41/44) abstained from drinking after treatment by the TMPs with only 6.7% (3/44) continuing to drink but less amounts. All participants described additional benefits after treatment including improvement in health, family relations and image in society.People who were treatment for alcohol drinking problems by traditional healers using plant derivatives in this study described personal and social benefits after stopping drinking. This calls for further research to the plants used.